Application and Influence of Information Technology to Support the Tourism Village Marketing Strategy - Mari Maryati; Andreas Bobola Cepi Ikun; A Matitaputty; R Alfarizi (Peneliti.net, 2021)
The purpose of this research is to improve the application and influence of information technology on tourism village marketing strategy. The use of descriptive methods in this study with interviews to get information related to this research, such as culture, traditional dance, traditional food and local handicraft products of the community in the tourist village. The results of this study show that by applying information technology to the marketing strategy of tourism villages will increase the economic income of local people in tourist villages and attract local and foreign tourists to visit. The conclusion obtained in this research is that the application of information technology has a positive impact on the marketing strategy of tourism villages in improving the economic growth of tourist village communities